Revitalizing Aceh language through writing skills using CIRC learning model and Canva media - Cut Santika Santi; M. Kasir (International Journal of Advances in Educational Research, 2024)
This study aims to determine students' ability to write persuasive text using Aceh language through the Cooperative Integrated Reading and Composition (CIRC) learning model and poster media. Writing persuasive text using language and spelling in the text must follow the Acehnese Latin script. Posters with invitations are intensively written using Indonesian and even foreign languages. The use of the Acehnese language has shifted at this time. This is in accordance with Statistics Indonesia (BPS) data, namely, the use of Acehnese local language is reduced among post-gen Z people born in 2013 and above compared to the pre-boomer generation (before 1945). This is based on the 2020 population census long-form report. The use of local languages by post-gen Z (2-9 years old) is 64.36 percent. This figure is much reduced compared to the pre-boomer generation (over 75 years old), whose number reached 89.93 percent. The study results show that out of thirty students who participated in the learning process, two got a score range of less than 69 with insufficient criteria. Six students get a score range of 70-79 with good enough criteria. Ten students get a score range of 80-89 with good criteria. Furthermore, twelve students get a score range of 90-100 with excellent criteria. Based on these results, it can be seen that students' ability to write Acehnese using CANVA media generally gets good criteria. The CIRC learning model makes a solution to improve students' writing skills. However, in the learning process, researchers still find some students who are less capable of expressing ideas in writing, where students are still minimal in choosing words.